Memory Complaints and Cognitive Decline: Data from the GUIDAGE Study1. - Dardenne, Sophie; Delrieu, Julien; Sourdet, Sandrine; Cantet, Christelle; Andrieu, Sandrine; Mathiex-Fortunet, Hélène; Fougère, Bertrand; Vellas, Bruno (J Alzheimers Dis, 2017)
BACKGROUND: Subjective cognitive decline (SCD) may be a very early symptom of Alzheimer's disease (AD) and may be associated with a cognitive decline in a cognitively normal population. The McNair and Kahn Scale was used to assess memory complaints in the GuidAge study. OBJECTIVE: Our objectives were to examine if the McNair and Kahn Scale can predict cognitive decline and to screen which (if any) of the question(s) of this scale would better predict this cognitive decline. METHODS: The GuidAge study was a phase III, multicenter, randomized, double blind, placebo-controlled study. Individuals aged 70 years and older, without cognitive impairment (Clinical Dementia Rate (CDR = 0)) at baseline who had spontaneously reported SCD were included in this study. The 20-item version of the McNair and Kahn Scale was used to assess SCD and a standardized neuropsychological assessment was used to assess the cognitive status. RESULTS: 1,307 patients with SCD and with CDR = 0 at baseline were included. During the 5 years of follow-up, 519 patients showed cognitive decline. Incidence of aggravation score of CDR was 13.40% person years (95% CI [12.24-14.56]). Results showed a significant relationship between the McNair and Kahn Scale score and decline in cognitive performance (HR 1.012; 95% CI [1.002-1.021]; p = 0.0156). Among the 20 items, 5 were statistically significant to predict cognitive decline after adjustment. CONCLUSION: SCD is a promising indicator of memory impairment. Our study found that using the McNair and Kahn scale can predict cognitive decline. A 5-item version of this scale could be used to screen patients in clinical practice and in clinical research.